PERKEMBANGAN GOLDEN AGE DALAM PERSPEKTIF PENDIDIKAN ISLAM - Prasetiawan, Ahmad Yusuf (Universitas Islam Negeri Raden Intan Lampung, 2019)
Child development, symbols and duties has not been widely understood, even though education is based on the child's developmental level will be quickly brought to success.This study aims to unravel the concept of a golden age, urgency and handling in Islamic educational perspective. The method used in this paper is the study of literature (theoretical studies), equipped with field observations.The results showed that the golden age in the perspective of Islamic education is the future of nature, where the child has not been contaminated by lust, pre puberty, and age under 13 years, as the hadith of the Prophet, who ordered the hit children when not working on prayer. Good handling is in line with the rights and obligations of the child. Learning methods that stimulate kekiuatan tep is analytical, systematic and rationality.